Komunikasi Petugas Haji di Era Digital: Studi Kasus Kabupaten Deli Serdang dalam Kerangka Smart Governance - Ferry, Muhammad; Kholil, Syukur (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study explores the dynamics of organizational communication among hajj officers in Deli Serdang Regency within the context of Indonesia's digital transformation and smart governance agenda. It addresses the research question: how do local hajj officers adapt their communication practices in response to digital demands and multi-agency coordination challenges? Using a qualitative case study method, data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that while digital platforms such as e-Hajj and e-Penkin improve data transparency and reporting efficiency, they also present challenges related to digital literacy, fragmented inter-agency communication, and cultural resistance to change. The study concludes that adaptive and inclusive communication strategies grounded in empathy and Islamic values are essential for effective service delivery, especially for elderly and disabled pilgrims. This research contributes a contextualized understanding of religious public service communication in decentralized, digitally evolving settings.